Changes in drug load during lacosamide combination therapy: A noninterventional, observational study in German and Austrian clinical practice. Issue 3 (22nd June 2019) - Reinhardt, Fritjof; Weber, Yvonne G.; Mayer, Thomas; Luef, Gerhard; Joeres, Lars; Tennigkeit, Frank; Dedeken, Peter; De Backer, Marc; Hellot, Scarlett; Lauterbach, Thomas; Webers, Tanja; Arnold, Stephan
Abstract: Introduction: Effects of antiepileptic drug (AED) load changes in patients with focal seizures have not been well evaluated. Methods: SP1065 (NCT01673282) was a noninterventional, prospective, observational study conducted in a clinical practice setting. Patients (aged ≥18 years) with focal seizures were enrolled within 7 days of being prescribed adjunctive lacosamide. Observation period was 6 months. Drug load was assessed using percentage change in ratio of actual prescribed dose and World Health Organization defined daily dose (DDD) for concomitant AEDs and all AEDs (including lacosamide). Subgroups were defined for patients with at least one concomitant sodium channel–blocking AED (SCB [+]) and those without (SCB [−]). Results: A total of 311 patients were assessed for safety, 302 for measurement of drug load, and 240 for effectiveness. Ratio of AED dose to DDD decreased for concomitant AEDs (−9.6%) and increased for all AEDs (including lacosamide; 15.5%). Median reduction in focal seizure frequency per 28 days was 100% (range: −100, 2275.8). 70.4% and 61.7% of patients had a ≥50% or ≥75% reduction in seizure frequency, respectively; 50.8% became seizure‐free. In the SCB (+) subgroup (n = 149), ratio of AED dose to DDD decreased for concomitant AEDs (−15.0%) and increased for all AEDs (10.7%). In the SCB (−) subgroup (n = 153), ratio of AED dose to DDD decreased for concomitant AEDs (−4.4%) and increased for all AEDs (20.2%). Fifty‐seven patients (18.3%) reported ADRs, most commonly dose >400 mg/d (7.1%). Seventeen patients (5.5%) had ADRs leading to discontinuation. Significance: Addition of lacosamide resulted in reduction of concomitant AED drug load regardless of whether concomitant AEDs were SCB (+) or SCB (−). These results indicate that addition of lacosamide in patients with focal seizures could allow clinicians to withdraw or reduce the dose of less well‐tolerated or less effective AEDs.